Analisis Penggunaan Dana Desa Berdasarkan Permendesa PDTT Nomor 16 Tahun 2018 Tentang Prioritas Penggunaan Dana Desa Tahun 2019 - Panji Setiawan; Badaruddin Badaruddin; Muryanto Amin (PERSPEKTIF, 2022)
The purpose of this study was to find out how to arrange use, implementation of use, types of proposals that developed at the village annual Musrembang forum, inhibiting factors from implementation and motives of stakeholders/related parties in encouraging the implementation of DD use based on Permendesa Pdtt. 16/2018 as a reference for Timbang Jaya Village, Bahorok District and Paluh Pakih Babussalam Village, Batang Serangan District. The method used in this research is a survey with observation techniques, in-depth interviews and literature study methods. The results of the study stated that the method of arranging the use of DD in Timbang Jaya Village, Bahorok District and Paluh Pakeh Babussalam Village, Batang Serangan District was appropriate. Implementation of the use of DD based on Permendesa Pdtt No. 16/2018 has not been fully implemented or has not become a reference for villages in carrying out development. The types of proposals that developed at the village's annual Musrembang forum became inhibiting factors from implementation, because they were dominated by proposals for infrastructure development activities that were not related to the priority provisions for the use of DD regulated by Permendesa Pdtt. 16/2018, while the motives of the stakeholders/related parties are so that there is integration between village development planning and national, provincial, and district/city development planning and so that the use of DD does not violate the provisions of applicable regulations.